Epigenetic Regulation at the Interplay Between Gut Microbiota and Host Metabolism - Miro-Blanch, Joan; Yanes, Oscar (Frontiers in Genetics, 2019)
Gut microbiota communities have coevolved for millions of years in a symbiotic relationship with their mammalian hosts. Elucidating and understanding the molecular mechanisms by which microbiota interacts with its host and how this contributes to the host ecosystem homeostasis is crucial. One of these molecular relationships is the so-called chemical crosstalk between microbiota and host metabolisms, which includes the poorly explored epigenetic regulation of host tissues, comprising DNA methylation and histone marks, by the metabolic activity of gut microbiota in response to changes in diet. Epigenetic marks are partly regulated by enzymes such as methylases and acetylases, whose activity depend on host and microbiota metabolites that act as substrates and cofactors for these reactions. However, providing a complete mechanistic description of the regulatory interactions between both metabolisms, and the impact on the expression of host genes through an epigenetic modulation, remains elusive. This article presents our perspective on how metabolomic, metagenomic and epigenomic data can be integrated to investigate the ‘microbiota-nutrient metabolism-epigenetics axis’. We also discuss the implications and opportunities this knowledge may have for basic research and applied science, such as the impact on the way we structure future research, understand and prevent diseases like type 2 diabetes or obesity.